New species and new records of thelotremoid Graphidaceae (Ascomycota: Ostropales) from Thailand - Papong, Khwanruan Butsatorn; Mangold, Armin; Lücking, Robert; Lumbsch, H. Thorsten (Phytotaxa, 2014)
Six new species of thelotremoid Graphidaceae are described from Thailand. Leucodecton confusum Papong, Mangold & Lücking has a densely corticate thallus and small, lepadinoid ascomata with double margin producing small, hyaline, submuriform ascospores. Ocellularia cerebriformis Papong, Lücking & Lumbsch is characterized by a brain-like, folded thallus surface, in combination with small, (sub-)muriform ascospores and protocetraric acid chemistry. Ocellularia kohphangangensis Papong, Mangold & Lücking features an unusual combination of small, brown, submuriform ascospores and the cinchonarum unknown chemistry. Ocellularia pseudopapillata Papong, Mangold & Lücking differs from O. papillata in the uneven-verrucose thallus, the thin, indistinctly fissured proper margin of the ascomata, and the carbonized columella. Ocellularia salazinica Papong, Mangold & Lücking is characterized by the presence of salazinic acid (a rare substance in Graphidaceae), in combination with ascomata resembling those of Rhabdodiscus, and comparatively large, muriform ascospores. A further species of Ocellularia, O. subdolichotata Papong, Mangold & Lumbsch, has a smooth, white thallus, prominent, columellate and carbonized ascomata, large, transversely septate ascospores (smaller than in O. dolichotata), and lacks secondary substances. The following 11 species are new records for Thailand: Chapsa discoides (Stirt.) Lücking, Glaucotrema glaucophaenum (Kremp.) Rivas Plata & Lumbsch, Leucodecton anamalaiense (Patw. & C. R. Kulk.) Rivas Plata & Lücking, Ocellularia fumosa (Ach.) Müll. Arg., O. granulifera (Kremp.) Müll. Arg., O. violacea Räsänen, O. viridipallens Müll. Arg., Rhabdodiscus subcavatus (Nyl.) Rivas Plata & Lumbsch, Stegobolus berkeleyanus Mont., Thelotrema defossum (Müll. Arg.) Mangold, and T. subadjectum Mangold.